Correlation between electroretinography, foveal anatomy and visual acuity in albinism - Hu, Zhaohui; Wang, Kai; Bertsch, Morgan; Dunn, Taylor; Kehoe, Taylor; Kemerley, Andrew D.; Helms, Megan; Bhattarai, Sajag; Pfeifer, Wanda; Scheetz, Todd E.; Drack, Arlene V. (Documenta ophthalmologica, 2019)
Background Albinism patients have poor visual acuity in addition to hypopigmentation. Their foveal anatomy is abnormal, but correlation with function is incompletely understood. This study correlates retinal electrophysiology, visual acuity and optical coherence tomography (OCT) anatomy in albinism patients and compares with age-similar controls. Methods Institutional Review Board approval was obtained (IRB# 201408782). Patients were recruited from clinical practice. Inclusion criteria were at least three clinical features of albinism including iris transillumination, nystagmus, fundus hypopigmentation, or foveal hypoplasia on OCT and/or molecular genetic confirmation. Diagnosys (Lowell, Mass) full-field ERG (ffERG) and VERIS multifocal ERG (mfERG; Electro-Diagnostic Imaging, Milpitas, California) were obtained using standard International Society for Clinical Electrophysiology of Vision protocols. The mfERG protocol was a 4-min 103-hexagon protocol covering approximately 40° in diameter of central retina. Control subjects without albinism were recruited by in-hospital notices and invitations in clinic. OCT central thickness was recorded, and an OCT foveal score was calculated. Nonparametric permutation testing was utilized to determine the statistical significance. Results A total of 16 albinism patients and 19 age-similar controls were recruited. Four of 16 albinism patients had no nystagmus. Seventeen non-albinism controls had no ocular disorder other than refractive error. Two controls had infantile nystagmus with normal maculas on OCT. There was no statistically significant difference in mfERG amplitude or latency between albinism patients with or without nystagmus (lowest p = 0.68; 0.54, respectively). mfERG: 12 of 16 (75%) albinism patients had average ring 1 amplitudes within one standard deviation of controls despite having abnormal foveal anatomy on OCT. Patients averaged shorter latencies in rings 1 and 2 than controls ( p = 0.005, p = 0.02). Patients averaged higher amplitudes than controls in rings 4, 5 and 6 ( p = 0.03, p = 0.006, p = 0.004). There was no significant correlation between visual acuity and mfERG amplitudes in any ring (smallest p = 0.15). ffERG: Patients averaged higher amplitudes on 30 Hz flicker ( p = 0.008). In all conditions, albinism patients had higher amplitude a-waves ( p ≤ 0.03). B-waves were higher amplitude than controls in light-adapted 3.0 ( p = 0.03). There was no statistical correlation between ffERG amplitudes and visual acuity (smallest p = 0.45). OCT: In albinism patients, thicker central macula on OCT correlated with lower mfERG amplitudes in all rings except for ring 1 ( p < 0.05) and lower ffERG a-wave amplitudes on dark-adapted 0.01 ( p = 0.003). Macular thickness on OCT did not correlate with visual acuity ( p = 0.51); OCT foveal score did ( p = 0.0004). Conclusions Amplitude of mfERG does not correlate with visual acuity in any ring in patients with albinism. The slope of the change in amplitude from central to peripheral rings on the mferg is significantly different in albinism patients versus controls whether or not nystagmus is present. The decreased slope of change in amplitudes from center to periphery of the macula in albinism patients indicates changes in macular topography that are more important to visual deficits than the foveal depression